Ekokiritik Sastra Dalam Buku Anak-Anak Seribu Sungai Jilid 1-5 Karya Rahman Hafiz Al Mubaraq - Putri Apridah; Noor Indah Wulandari (Universitas Pakuan, 2026)
LITERARY ECOCRITICS IN THE CHILDREN'S BOOK A THOUSAND RIVERS VOLUME 1-5 BY RAHMAN HAFIZ AL MUBARAQ Children's literature plays a strategic role in building ecological awareness from an early age. Rahman Hafiz Al Mubaraq's book